Inovasi Teknologi dalam Upaya Peningkatan Nilai Jual melalui Diversifikasi Produk Olahan Jagung pada Kelompok Tani di Kabupaten Soppeng - Ismail, Ismail; Rahmah, Puji; Minarti, Asnia (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Maize commodities in Watu toa Village are still widely managed as raw materials for animal feed and are generally marketed in primary form either in the form of dried corn flakes or sold in the form of fresh corn at low prices. This is due to the limited knowledge of the community in applying technology to develop the potential of maize, resulting in low income for farmers. Maize price Daily transactions Maize is traded at USD490.25 per bushel. In rupiah terms, this is equivalent to IDR 2,992.5 per kg.  Despite the abundant maize harvest in Watutoa village, this has not been able to increase farmers' income. This is because the processing of corn for selling value is still very limited where farmers only sell their corn agricultural products directly at low prices and on the other hand the marketing method is also still limited to the area around Watutoa village. to help solve the existing problems, community service is carried out to apply diversified corn processing technology. The purpose of the implementation of the service activities carried out is to increase the value of processed corn production into selling value by verifying processed corn based on the application of appropriate technology. The implementation methods carried out are socialisation, training, evaluation and mentoring. The results of the community service activities of corn processed diversification can increase community knowledge about corn diversification, increase the type of processed corn production into three processed corn in the form of popcorn, corn flour, and corn sugar. The results of processed corn diversification of 1 kg of raw materials at a price of 2500 rupiah are processed into popcorn as much as 1800 grams or 18 plastic packs of 100 grams with an increase in income from 2500 rupiah to Rp.90,000. for the results of corn flour diversification from raw materials as much as 142 grams at a price of 370 rupiah into flour as much as 100gram at a price of 4500 rupiah. And for the diversification of corn sugar from 1 Kg of corn raw material processed into liquid sugar produces 700 ML at a price of 17,000 rupiah.